500 crochet stitches : the ultimate crochet stitch bible. (St. Martin's Griffin, 2015)
Presents an introduction to crocheting, discussing tools, equipment, basic and advanced stitches, edgings, and trims, with illustrations and detailed instructions for five hundred stitches.